PERCEPTIONS OF THE USE OF THE BLACK BOX.AI DIGITAL PLATFORM AS A LEARNING MEDIUM IN THE DIGITAL AGE AMONGST STUDENTS OF THE FACULTY OF ENGINEERING, ABDURRAB UNIVERSITY, COHORT OF 2022 - Fenny Anita; Dewi Salfiati; Muhammad Hanif Ahda (Universitas Dharmawangsa Medan, 2026)
In this study, perception is defined as an individual’s cognitive process of receiving, organising and interpreting information. This research aims to explore the perceptions of 2,022 students from the Faculty of Engineering at Universitas Abdurrab regarding the use of the digital platform Black Box.ai as a learning medium in the digital age. The study employed a descriptive qualitative approach based on Robert J. Sternberg’s theory of perception, which encompasses sensation, perception, recognition, top-down processing and bottom-up processing. The research informants comprised six students from the Faculty of Engineering at Universitas Abdurrab, class of 2022, who had experience using Black Box.ai in their learning activities. Data were collected through in-depth interviews, observation and documentation. The data were analysed using the Miles and Huberman model, which comprises data reduction, data display, drawing conclusions, and verification. The findings indicate that students generally hold positive perceptions of the use of Black Box.ai as a digital learning medium. The platform is considered user-friendly, with a simple interface and navigation system, and is helpful in searching for, understanding, and processing course materials, particularly those that are technical and complex. The available features are perceived to improve learning efficiency, speed up information retrieval, and enhance students’ understanding of learning materials compared to conventional learning methods. Based on Sternberg’s theory of perception, students’ prior learning experiences, knowledge, and academic needs influence how they evaluate the benefits and effectiveness of the platform. Nevertheless, students emphasised that lecturers continue to play a vital role in providing explanations, clarification, and reinforcement of learning materials. Overall, Black Box.ai is perceived as having significant potential to support the quality of learning in the future when used wisely and integrated with the role of educators.